2019
DOI: 10.7759/cureus.6380
|View full text |Cite
|
Sign up to set email alerts
|

The Role of EkoSonic Endovascular System or EKOS® in Pulmonary Embolism

Abstract: Pulmonary embolism has become a cause of great concern to health care professionals. Despite strides in research and availability of sensitive diagnostic tests, the mortality and morbidity related to this entity continues to cause tremendous economic burden. Patients present with an array of symptoms ranging from mild dyspnea to hemodynamic instability and even death. Prompt recognition of symptoms along with early risk stratification can be lifesaving. Management focuses on achieving hemodynamic stability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…One of the most important advantages of this approach, as seen in this case, is the avoidance of potential complications of systemic anticoagulation therapies. 13 This is especially beneficial when managing post-operative patients where systemic therapy may be contraindicated. However, although it has been found that catheter-directed therapy had less in-hospital mortality than systemic thrombolysis in treatment PE, the evidence for pediatric population is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important advantages of this approach, as seen in this case, is the avoidance of potential complications of systemic anticoagulation therapies. 13 This is especially beneficial when managing post-operative patients where systemic therapy may be contraindicated. However, although it has been found that catheter-directed therapy had less in-hospital mortality than systemic thrombolysis in treatment PE, the evidence for pediatric population is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for using systemic thrombolysis with half-dose tPA for SPE was established by the Moderate Pulmonary Embolism Treated With Thrombolysis (MOPETT) trial, which showed that half-dose tPA plus systemic AC decreased pulmonary hypertension incidence, PA pressures, and hospital stay [ 5 ]. Even the PERT Consortium guidelines suggest using low-dose tPA for SPE cases with evidence of clinical deterioration based on vital signs, the severity of RV dysfunction, tissue perfusion, and gas exchange in the absence of absolute contraindications to thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients with severe aortic stenosis require relief of outflow tract obstruction with some form procedure including balloon aortic valvotomy, transcatheter aortic valve replacement depending upon their ability to tolerate these procedures. Additonally, survivors of acute pumonary embolism need definitive treatment using procedure like transcatheter guided thrombolysis (EKOS) or pulmonary thromboendarterectomy utilizing cardiopulmonary bypass support [102].…”
Section: Definitive Treatment Of Underlying Causesmentioning
confidence: 99%